El Niño‐Southern Oscillation‐Induced Variability of Terrestrial Gross Primary Production During the Satellite Era. Issue 8 (3rd August 2019) - Zhang, Yulong; Dannenberg, Matthew P.; Hwang, Taehee; Song, Conghe
Abstract: Terrestrial gross primary production (GPP) is the largest carbon flux entering the biosphere from the atmosphere, which serves as a key driver of global carbon cycle and provides essential matter and energy for life on land. However, terrestrial GPP variability is still poorly understood and difficult to predict, especially at the annual scale. As a major internal climate oscillation, El Niño‐Southern Oscillation (ENSO) influences global climate patterns and thus may strongly alter interannual terrestrial GPP variation. Using a remote sensing‐driven ecosystem model with long‐term satellite and climate data, we comprehensively examined the impacts of ENSO on global GPP dynamics from 1982 to 2016, focusing on lag effects of ENSO and their spatial heterogeneity. We found a clear seasonal lag effect of previous‐year ENSO indices on current‐year global GPP variability. The composite Oceanic Niño Index in the previous‐year's August‐October showed the strongest correlation with global annual GPP ( R = −0.51, p < 0.01). Spatially, 20.1% and 11.7% of vegetated land area showed significant negative and positive correlations with the ENSO cycle, respectively. ENSO effects on annual GPP exhibited diverse seasonal evolutions, and the timings of peak ENSO influences were heterogeneous across the globe. Annual GPP from TRENDY land surface model ensemble did not capture the major lag effects of ENSO identified in the satellite‐derived GPP and top‐down‐based land sink. Despite the complexity of the climate system, our efforts linking ENSO with global GPP dynamics provide a simple framework to understand and project climatic influences on the terrestrial carbon cycle. Key Points: The composite ONI in the previous‐year's August‐October shows the strongest correlation with global annual GPP ENSO effects on annual GPP exhibit diverse seasonal evolutions, and the timing of peak ENSO influences are heterogeneous across the globe TRENDY ensemble appears to miss the major lag effects of ENSO identified in the satellite‐derived GPP and top‐down‐based land carbon sink